Genetic improvement of F1 hybrids in anthurium andreanum linden - Pravin RS (Department of Plant Breeding and Genetics, College of Agriculture, 2004)
The present study, ‘Genetic improvement of F1 hybrids in Anthurium andreanum Linden’ was undertaken to improve specific commercial characters such as erect, long inflorescence axis, deep blisters of spathe and short downward candles of ten selected F1 hybrids in anthurium. The analysis of variance revealed significant variation among the fourteen genotypes for the seventeen characters studied. This reveals the high genetic potential for the improvement in this crop. Variability studies indicated high phenotypic and genotypic coefficients of variation for the characters number of suckers per plant, pollen fertility and duration of male phase. The characters with high heritability coupled with high genetic advance values were found for characters number of suckers per plant, pollen fertility and pollen size. These characters are therefore controlled by additive gene action and amenable to genetic improvement through selection. Plant height was found to have highly significant positive phenotypic correlation with number of suckers per plant, leaf size, internode length, number of spadices per plant and pollen fertility. Duration of female phase showed positive genotypic correlation with all characters except days to initiation of female phase. The environmental correlations were absent for almost all pairs of characters except for a few characters .